Karakterisasi Silika Fly Ash Yang Diperoleh Dengan Metode Ekstraksi - Fika Rahma Yuni; Lita Darmayanti; Dewi Fitria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This research was conducted to investigate the characteristics of silica extracted from Palm Oil Fly Ash.. The obtained silica involves the extraction process using an alkaline solution and an acid solution. It was found that the highest yield was obtained from extraction using a solid/liquid ratio of 1:12 with extraction time of 120 minutes. Silica characterization using XRF shows the element or compound contained in the sample.. Kata kunci : fly ash, silica, extraction, solid/liquid ratio, stirring time